Effect of an alkali treatment on the development of cellulose pulp-based gel-like dispersions in vegetable oil for use as lubricants. (July 2018) - Martín-Alfonso, J.E.; López-Beltrán, F.; Valencia, C.; Franco, J.M.
Abstract: The main aim of this study was to elucidate the influence of an alkali treatment on the rheological and tribological properties, and microstructure, of cellulose pulp-based gel-like dispersions potentially usable as biodegradable lubricating greases. For this purpose, cellulose pulp was treated with sodium hydroxide under different conditions of alkali concentration (20, 30 and 40%), temperature (20, 45 and 75 °C) and contact time (1 and 2 h). Favourable conditions relative to the rheological response of a commercial lithium lubricating grease used as benchmark were found to be 40% NaOH, 20 °C and 2 h. Gel-like dispersions with acceptable lubrication properties in terms of consistency indices, mechanical stability, and frictional and wear performance, were obtained by using a 6–7% (w/w) proportion of cellulose pulp. Highlights: Development of cellulose pulp-based gel-like dispersions in vegetable oil. The role of alkali treatment on the rheological and tribological properties. Effective method for improving the compatibility of fibres and vegetable oil. Comparative study with a commercial lithium grease.